2012
DOI: 10.1182/blood-2012-05-433540
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring chronic lymphocytic leukemia progression by whole genome sequencing reveals heterogeneous clonal evolution patterns

Abstract: Chronic lymphocytic leukemia is characterized by relapse after treatment and chemotherapy resistance. Similarly, in other malignancies leukemia cells accumulate mutations during growth, forming heterogeneous cell populations that are subject to Darwinian selection and may respond differentially to treatment. There is therefore a clinical need to monitor changes in the subclonal composition of cancers during disease progression. Here, we use whole-genome sequencing to track subclonal heterogeneity in 3 chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
314
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(337 citation statements)
references
References 38 publications
20
314
0
3
Order By: Relevance
“…The existence of these dominant behaviours exhibited by the u 1 or u 2 populations are consistent with the principle of competitive exclusion of clonal sub-populations in heterogeneous tumours (Egan Keats et al, 2012;Leith et al, 1989). In Fisher et al (2013) the authors interpreted the experimental data, which showed suppression and reappearance of cancer clones in myeloma patients (Keats et al, 2012) and chronic lymphocytic leukaemia patients (Schuh et al, 2012), by suggesting that two subclones can exist in a dynamic equilibrium. While all these experimental studies record the survival/suppression of tumour clones in various cancers, they do not offer a mechanistic explanation for the factors that could lead to these behaviours.…”
Section: Conclusion and Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The existence of these dominant behaviours exhibited by the u 1 or u 2 populations are consistent with the principle of competitive exclusion of clonal sub-populations in heterogeneous tumours (Egan Keats et al, 2012;Leith et al, 1989). In Fisher et al (2013) the authors interpreted the experimental data, which showed suppression and reappearance of cancer clones in myeloma patients (Keats et al, 2012) and chronic lymphocytic leukaemia patients (Schuh et al, 2012), by suggesting that two subclones can exist in a dynamic equilibrium. While all these experimental studies record the survival/suppression of tumour clones in various cancers, they do not offer a mechanistic explanation for the factors that could lead to these behaviours.…”
Section: Conclusion and Discussionmentioning
confidence: 83%
“…In this study, we will investigate the role of cancer mutation on the possibility of clonal competition with alternating dominance or even competitive exclusion between two cancer cell sub-populations (as discussed before, these types of competition have been observed experimentally (Leith et al, 1989;Keats et al, 2012;Schuh et al, 2012)). To this end, we will introduce a nonlocal model for cell-cell and cell-matrix adhesion for two populations of cells (this model is a generalization of the models in Armstrong et al (2006); Gerisch & Chaplain (2008); Painter et al (2015)).…”
Section: Introductionmentioning
confidence: 99%
“…Probes targeting all coding exons or hotspot regions of 27 known CLL driver genes and/or genes previously reported in EGR2-mutated CLL 19,29,[37][38][39][40][41][42][43][44] were designed using Agilent"s SureDesign service (https://earray.chem.agilent.com/suredesign/home.htm, Supplemental Table S4). …”
Section: Analysis Of Concurrent Mutations By Targeted Deep-sequencingmentioning
confidence: 99%
“…It is not known at the moment whether the mutation order is important for the clinical course but similar to clonal, subclonal mutations may carry prognostic value [35]. Integrating genomic data from sequential samples, three types of CLL evolution were identified, which associate with patient's course: (i) no evolution, (ii) linear evolution, and (iii) branched evolution [9,11,26,[129][130][131][132]. Branched evolution is associated with disease evolution and dismal prognosis, probably because the generated genetic diversity allows for a more efficient selection of fitted cells.…”
Section: Intrapatient Heterogeneitymentioning
confidence: 99%